Design ethnography: methodological considerations for rebalancing socio-technical phenomena in CMS performativity - Jordaan, Leandra (Rhodes University, Faculty of Commerce, Department of Information Systems, 2020)
As a practitioner, I had been part of two Content Management System (CMS) Projects in a particular setting that did not deliver on the expected outcomes. The expected outcomes of the projects included streamlined processes, better access to information, functionalities to drive engagement, reduced time searching for information, and improved reusability of content. As I began to reflect on the projects, a certain discomfort developed when the social aspect was ignored in favour of the technological. I sought a better understanding, but I was unaware of the fact at first. The techno-centricity as a concept found in literature and my experience as content management (CM) practitioner "“ together informed my interest in rebalancing the social and the technological. Thus, I focused on conduct in performing of tasks and emphasised attention on the practices of experts who gave insight into context of CM and use. The research participants are communication practitioners who have the responsibility to communicate internally and externally on behalf of a publicly-funded university in South Africa. Guided by the abductive argument and literature, the key themes for the research focused on technology, individuals and the organisation. The focus on technology (CMS as a subfield of Information Systems) began with my involvement in two CMS Projects. What came to the fore was that the practitioner perspective, and thus their experiential knowledge are neglected in research and that it may be an over-emphasis on techno-centrism in CMS research. I sought to better balance the social and technological aspects. The second focus on individuals (communication practitioners) was to value the stakeholder who was considered representative of the worldviews of the community. I sought to support corporate communication practices in the task of relationship building with stakeholders. The findings showed that the culture of informatio sharing was low at the University. The third focus on the organisation (the University) was to prioritise the success of the communication undertaken by the University. I interrogated the role of power. I demonstrated how the role of power could be seen as productive and positive in the context of HE, the social reality of CUT, and this IS research itself. I positioned the research as interpretivistic. I used hermeneutics as a mode of analysis because as researcher-practitioner, I am part of the social reality of the research. A safeguard against my subjectivity was the use of Phronesis as an orientation to knowledge. An organisation with a shared understanding of ethics and values will balance instrumental rationality (scientific and technical reasoning) with value-rationality (moral reasoning about right and wrong actions). Phronesis is the virtue that should ensure ethical behaviour in actions, yet over time, social science research, in a quest to mimic the natural sciences, centred on episteme and techne. I constructed the lens by particularising the four value-rational questions of Flyvbjerg's contemporary Phronesis to the performative perspective of the research. My interest in social reality, as well as socio-technical aspects, have led to design-ethnography (D-E) to emerge as the most suitable and most appropriate approach to the research. D-E asked the prescriptive 'How' and descriptive 'What' questions, whilst the Flyvbjergian Phronesis lens brought focus on the 'Why' question. D-E emphasised the betterment of the interaction and synergy between research conducted and practice. My status as an immersed researcher needed careful consideration, and D-E accepted that a certain level of immersion is necessary, D-E has short interventional fieldwork, and D-E has future-oriented engagement. The contemporary Phronesis used in the research is to enact D-E and not an all-encompassing guide for doing Phronesis research The key contributions to the research are predominantly methodological. The claims draw on evidence focused on the three themes technology, individuals and organisation, and the phenomena of interest which are to rebalance the social and the technological in CM practices. The first claim is that immersion in the context is possible and supported by the specific particularised approaches to the research. The second claim suggests a way to rebalance the socio-technical nature of Information Systems (IS). The third claim suggests that there is a viewpoint for power that is not focused on power's oppressive nature which could see a diverging focus on power in IS research in future. In this viewpoint, the status quo of social reality is not questioned, nor are their emancipatory ambitions. The fourth and final claim suggests that Phronesis as a lens could enact D-E, which in turn is a method that assists in valuing the experience of the practitioner and the support of collaborative work. The research is recommended for IT/IS practitioners who prefer to value participants' views in design. The approaches used could be of value for researchers who consider the context of their research to be of higher importance than the generalisation of outcomes. Researchers who find themselves in the position of being immersed in the context but question the correctness of active engagement in the field may discover some value from the research approaches and my experience. Also, researchers or practitioners who have an interest in the balance between social and the technological aspects of IS projects. Researchers or practitioners interested in Phronesis, and perhaps the viewpoint of a lens may also find value in this research.
Keywords: Database management -- Social aspects; Information technology -- Social aspects; Management information systems -- Social aspects; Database management -- Philosophy; Information technology -- Philosophy; Management information systems -- Philosophy